(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Insertion of supraglottic airway devices such as AMBU LMA requires adequate anaesthetic depth to suppress airway reflexes while maintaining stable hemodynamics and respiratory function. Propofol is commonly used for this purpose, but adjuvants such as fentanyl and clonidine are frequently added to improve insertion conditions and reduce adverse effects. This study compares clonidine–propofol and fentanyl–propofol combinations. Methodology: This prospective randomized study was conducted in patients undergoing elective surgery requiring AMBU LMA insertion. Patients were allocated into two groups: Group F received fentanyl with propofol and Group D received clonidine with propofol. Standard monitoring was applied, and induction was achieved with propofol after administration of the study drug. Hemodynamic parameters (heart rate and mean arterial pressure), respiratory parameters (SpO₂), and ease of LMA insertion were recorded and analysed using appropriate statistical methods. Results: Clonidine–propofol provided better heart rate control and more stable mean arterial pressure compared to fentanyl–propofol, with statistically significant differences at multiple time points. Oxygen saturation remained stable and comparable in both groups. Hemodynamic fluctuations were lower in the clonidine group, indicating better sympatholytic response during induction and LMA insertion. Conclusion: Clonidine–propofol combination offers superior hemodynamic stability compared to fentanyl–propofol for AMBU LMA insertion, with comparable respiratory safety.